Cerebral microbleed distribution following cardiac surgery can mimic cerebral amyloid angiopathy. Issue 2 (13th July 2021) - De Sciscio, Michele; De Sciscio, Paul; Vallat, Wilson; Kleinig, Timothy
Abstract : Background and aims: Having anecdotally noted a high frequency of lobar-restricted cerebral microbleeds (CMBs) mimicking cerebral amyloid angiopathy (CAA) in patients with previous cardiac surgery (especially valve replacement) presenting to our transient ischaemic attack (TIA) clinic, we set out to objectively determine the frequency and distribution of microbleeds in this population. Methods: We performed a retrospective comparative cohort study in consecutive patients presenting to two TIA clinics with either: (1) previous coronary artery bypass grafting (CABG) (n=41); (2) previous valve replacement (n=41) or (3) probable CAA (n=41), as per the Modified Boston Criteria, without prior cardiac surgery. Microbleed number and distribution was determined and compared. Results: At least one lobar-restricted microbleed was found in the majority of cardiac surgery patients (65%) and 32/82 (39%) met diagnostic criteria for CAA. Valve replacement patients had a higher microbleed prevalence (90 vs 51%, p<0.01) and lobar-restricted microbleed count (2.6±2.7 vs 1.0±1.4, p<0.01) than post-CABG patients; lobar-restricted microbleed count in both groups was substantially less than in CAA patients (15.5±20.4, p<0.01). In postcardiac surgery patients, subcortical white matter (SWM) microbleeds were proportionally more frequent compared with CAA patients. Receiver operator curve analysis of a 'location-based' ratio (calculated as SWM/SWM+strictly-cortical CMBs), revealed an optimal ratio of 0.45 in distinguishing cardiac surgery-associated microbleeds from CAA (sensitivity 0.56, specificity 0.93, area under the curve 0.71). Conclusion: Lobar-restricted microbleeds are common in patients with past cardiac surgery, however a higher proportion of these CMBs involve the SWM than in patients with CAA.